Capacitação em saúde no sistema prisional : instituição legal e percepções de gestores e profissionais de saúde atuantes em Mato Grosso - Padilha, Weslen Santana (2018)
The legal apparatuses specific to the prison community reiterated the constitutional right of health and the implantation of health units in the System. These and others define the training strategies of the working teams, which require a critical and reflexive, propositive, committed, ethical and technically competent professional in the face of the demands of the complex context as of the institutions of the Prison System. This study aims to identify how and how the training of health professionals working in the Prison System of Mato Grosso has become effective, considering the specifics of the prison context. This qualitative research used two sources for the production of the data: Database, resulting from a matrix research on the subject coming from a field work carried out in three closed regime penitentiaries located in Cuiabá / MT, from April 2013 to February 2014, generating raw data from 22 interviews guided by semi-structured script with health professionals and 2 interviews with managers. Another source is the public domain Public Health Devices in the Prison System that address the issue of human resources training. The data were analyzed by the thematic analysis, identifying the nuclei of meaning and characteristics of the skills in the approximations with the Liberal and Progressive pedagogical tendencies (and respective aspects) proposed by Libâneo, as well as the nuances of the principles of the Permanent Education in Health. , some received the training days, months and years after the entry, in a fragmented and discontinuous way. Others did not receive any training and they learned on a day-to-day basis with the mentoring of those who were already active. Regarding the contents, they received information about general rights, security, feeling the need for themes that are closer to and pertinent to daily practice. The management shows nuances of improvisation in the actions of training, little articulated or institutionally strengthened. Training for health professionals in prisons is necessary as a democratic mechanism for team participation in order to value individual and collective knowledge, expanding the spaces for reflection and learning about professional practice, in the place where they take place and in a way permanent. As they are configured, the capacities distance themselves from the logic of the EPS, being punctual, fragmented predominating traditional methodology (liberal tendency) little sensitive to the concrete practice and emphasizing safety and discipline contents. Finally, it is important to have adequately trained and critical professionals to give effective responses to the prison community, recognizing care as a right to health. The training of health professionals working in the Prison System requires the articulation of intersectoral policies so as not to be restricted to bureaucratic formality, but socially to achieve the legal right conquered.